RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN MENGGUNAKAN PRESENSI SIDIK JARI (STUDI KASUS PADA PT. KUDA INTI SAMUDERA CABANG SURABAYA) - Satyawan, Angga Hanggar; Hariadi, Bambang; Amelia, Tan (Jurnal JSIKA, 2013)
PT. Kuda Inti Samudera is a company that provides, maintains, and operates heavy equipment in a port. PT. Kuda Inti Samudera has four branches, including Surabaya, Semarang, Makassar, and Banjarmasin. PT. Kuda Inti Samudera (Surabaya) has several divisions, such as Human Resource Development (HRD) and Finance Division. The Human Resource Development handles some activities, including recapitalize and create data report of employees’ presence, while the Finance Division handles some activities, such as create data report of employees’ salary. There are some problems in PT. Kuda Inti Samudera related with those two divisions, such as employees’ presence still done manually by using check-lock, so employees can do cheating when they absented. Similarly at the Finance Division, yet the data report between employees’ presence recapitulation from HRD and data report of employees’ salary still not integrated automatically. Based on the illustration above, it is necessary to create Payroll Information System using fingerprint for the presence that integrated and appropriated with PT. Kuda Inti Samudera (Surabaya), so cheating will not happen again during the process of employees’ presence. The results of the implementation of Payroll Information System using fingerprint in PT. Kuda Inti Samudera (Surabaya) has able to overcome the cheating of employees´ presence and produce integrated data report of employees’ presence and salary. Keywords : Information System, Presence, Fingerprint, Employee, Payroll